THE CONUNDRUM OF BEING CONFRONTED WITH A DIRE THYROTOXICOSIS ON THE MORNING OF CORONARY ARTERY BYPASS GRAFT SURGERY (CABG) - Thoulat, Mohamed Imran; Kamaruddin, Nor Azmi; Yunus, Alwi Mohamed (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND This case illustrates the management of an acute medical condition with complex comorbidities, highlighted by a patient with acute pulmonary oedema post-NSTEMI and severe preoperative thyrotoxicosis, undergoing urgent CABG. CASE A 52-year-old female with a history of myocardial infarction presented with an acute pulmonary oedema following an episode of NSTEMI. An urgent coronary angiogram revealed a thrombosed stent in the left anterior descending and left circumflex arteries. She was deemed a high-risk patient; hence, an urgent CABG was planned. However, on the morning of the planned surgery, she had tachycardia of 130/minute. Thyroid function tests showed elevated fT4 of 99.2 pmol/L (normal range: 12-22) and suppressed TSH <0.01 m IU/L (normal range: 0.4-4.5). At the insistence of the cardiothoracic surgeon who was concerned about an impending cardiogenic shock, the endocrinologist reluctantly agreed to allow the surgery to proceed with the following provisions: 1. Immediate loading with 10 drops of Lugol’s iodine, 100 mg IV hydrocortisone, 10 mg carbimazole, and 4 grams of cholestyramine 2. Heart rate was to be lowered with 80 mg of propranolol repeated every half an hour till the heart rate went to <100/min. 3. Surgery was to be delayed for a further 4 hours to allow for the anti-thyroid regimen to take effect whilst controlling the heart rate. Throughout surgery, the heart rate was maintained at 100/minute. Despite the risk of hemodynamic instability, the surgery was uneventful. The patient was kept in the ICU and eventually extubated 2. All the anti-thyroid regimens were continued diligently except for hydrocortisone which was stopped on POD 3. On POD 5, she developed an episode of atrial fibrillation which was promptly terminated with synchronised cardioversion. Notwithstanding the concern of a lifethreatening thyroid storm, her recovery was seemingly uneventful. On POD 9, her fT4 had steadily come down to 16.4 pmol/L and she was promptly discharged home with a maintenance dose of 10 mg carbimazole. CONCLUSION The successful outcome in this high-risk patient, achieved through a multidisciplinary approach, underscores the potential benefits and ongoing debate regarding the optimal strategy for such complex clinical scenarios.